2017
DOI: 10.3384/ecp17138188
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Oil Production from Homogenous North Sea Reservoirs with Inflow Control using OLGA/Rocx

Abstract: Advances in drilling technology have made long,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Proceedings of SIMS 2020 Virtual, Finland, 22-24 September 2020 with valves, packers, annulus, and production pipe, OLGA requires a "Flowpath" and "Pipeline" (Sund et al, 2017) as shown in Figure 7. For an accurate representation of the wellbore, two separate production pipes need to be defined to account for the annulus and production pipe.…”
Section: Olgamentioning
confidence: 99%
“…Proceedings of SIMS 2020 Virtual, Finland, 22-24 September 2020 with valves, packers, annulus, and production pipe, OLGA requires a "Flowpath" and "Pipeline" (Sund et al, 2017) as shown in Figure 7. For an accurate representation of the wellbore, two separate production pipes need to be defined to account for the annulus and production pipe.…”
Section: Olgamentioning
confidence: 99%